Young Learners’ Motivation in Learning English: A Survey at Lawawang Village, Masela Island - Southwest Maluku - Tiwery, Yulina (Prodi Pendidikan Bahasa Inggris, Program Studi Diluar Kampus Utama (PSDKU) Unpatti-MBD, 2020)
Motivation is known as the success key to do and to reach something including the ways a learner learns something. So that, it is very important to conduct this type of research in order to know what kinds of motivation do the young learners have and which kinds of motivation affects mostly the ways they learn English. The research design that the researcher conducted was survey. The sample for this research was taken randomly. It was 20 young learners that consist of 3 people for age 8, 5 people for age 9, 2 people for age 10, 4 people for age 11, 5 people for age 12, and 1 person for age 13. The research was done in October 21st to 28th 2020. The instrument used to collect the data was questionnaire. Each kind of motivation consisted of 5 items. So, the total items that the participants had to fill were 10. Based on the calculation of the total mean score for each kind of motivation namely intrinsic and extrinsic, the result shows in learning English by themselves (autodidact) or by other people, the young learners have higher intrinsic motivation than the extrinsic motivation with the total mean score is 4.08. While, the total mean score which gotten through the calculation of 5 items in extrinsic motivation is 3.10 which indicates moderate level.